Technological adaptation of the MBKM Kampus Mengajar VII Program for Teknologi Pendidikan FIP UNM students - Pattaufi Pattaufi; I Made Tegeh; Farida Febriati (Inovasi Kurikulum, 2025)
The Merdeka Belajar Kampus Merdeka (MBKM) Program is integral to higher education in Indonesia. This program provides opportunities for students to gain practical experience in the field. This study explores the technology adaptation process of Teknologi Pendidikan students at FIP UNM in the MBKM Kampus Mengajar VII Program. In addition, this study also identifies the challenges faced by students and the strategies used to overcome them. Using a qualitative approach with a case study design, data were collected through in-depth interviews, participatory observations during field activities, and analysis of related documents. The data obtained are explained through the reduction, presentation, and interpretation stages. The analysis focused on key themes, such as technology adaptation strategies, challenges faced by students, and the implementation of the MBKM program in the future. This study is expected to provide a more comprehensive insight into the technology adaptation process of Educational Technology students at FIP UNM during the MBKM Kampus Mengajar VII Program. These findings will provide valuable contributions to higher education institutions in improving technology integration in field programs and guiding students and teachers in facing the challenges of technology adaptation.   Abstrak Program Merdeka Belajar Kampus Merdeka (MBKM) merupakan bagian integral dari pendidikan tinggi di Indonesia. Program ini memberikan kesempatan bagi peserta didik untuk memperoleh pengalaman praktis di lapangan. Penelitian ini bertujuan untuk mengeksplorasi proses adaptasi teknologi mahasiswa Teknologi Pendidikan di FIP UNM dalam Program MBKM Kampus Mengajar VII. Selain itu, penelitian ini juga mengidentifikasi tantangan yang dihadapi peserta didik serta strategi yang digunakan untuk mengatasinya. Menggunakan pendekatan kualitatif dengan desain studi kasus, data dikumpulkan melalui wawancara mendalam, observasi partisipatif selama kegiatan lapangan, dan analisis dokumen terkait. Data yang diperoleh dijelaskan melalui tahapan reduksi, penyajian, dan interpretasi. Analisis difokuskan pada tema-tema utama, seperti strategi adaptasi teknologi, tantangan yang dihadapi mahasiswa, serta penerapan program MBKM di masa depan.Penelitian ini diharapkan dapat memberikan wawasan yang lebih komprehensif tentang proses adaptasi teknologi mahasiswa Teknologi Pendidikan di FIP UNM selama Program MBKM Kampus Mengajar VII. Temuan ini akan memberikan kontribusi berharga bagi perguruan tinggi dalam meningkatkan integrasi teknologi pada program-program lapangan, serta menjadi panduan bagi mahasiswa dan pengajar dalam menghadapi tantangan adaptasi teknologi. Kata Kunci: adaptasi teknologi; Kampus Mengajar; MBKM; teknologi pendidikan